The Relationship between Learning Methods with Children’s Interest in Koto Tuo Kenagarian Lubuk Tarok Sijunjung District - Muhammad Ikbal; Vevi Sunarti (Universitas Negeri Padang, 2020)
This research is motivated by the low interest in learning of students studying the Al-Quran to Surau in Koto Tuo, Kenagarian Lubuk Tarok, Sijunjung District. This is caused by the unattractive learning methods applied by teachers in Surau. This study aims to see an overview of learning methods applied in Surau, an overview of student's interest in learning to read the Al-Quran to the Surau, and see the relationship of the learning methods with students interest in learning to Surau in Koto Tuo, Kenagarian Lubuk Tarok, Sijunjung District. This research is quantitative research with correlational type. The population in this study were all students registered at Surau that were still active in Koto Tuo, Kenagarian Lubuk Tarok, Sijunjung District with a total of 96 people. Respondents in this study were 30 people. Then to determine respondents used a simple random sampling technique, many of the samples taken were 30% of the total population. Data collection techniques used in this study were questionnaires, while data collection tools in this study were questionnaire guidelines. Data analysis techniques using the formula percentage and product moment. The results of this study indicate that the learning methods applied in Surau are not attractive, students learning interest in studying Surau is very low, there is a significant relationship between the learning methods and the students learning interest in Surau. Advice is expected to Surau to oversee the development of the learning process and evaluate the learning process that has been completed so that it can better. Then it is also expected for teachers to increase their ability to apply interesting learning methods. And it is hoped that other variables that affect learning interest.Keywords: Learning Methods, Learning Interest, Surau